Towards Simplifying Arabic Grammar: Mahdi Al-Makhzumi as a Model - Salem Mohammed , Yazid; abi, abdessalem (El Omda in Linguistics and Discourse Analysis, 2026)
Abstract: In this article, the researchers aim to approach the achievement of Mahdi Al-Makhzoumi, who directed himself towards the model of ancient Arabic grammar and used the sword of criticism in it, hoping to reach a model free - in his view - from the flaws that he sees as impeding the control of Arabic grammar at the level of the rules and theoretical foundations on which Arabic grammar was based. The researchers found that Al-Makhzoumi, like many grammarians, started their criticism from a direct influence of what resulted from the Arab reception of modern linguistics, the general frameworks of which were set by the Swiss linguist Ferdinand de Saussure.Therefore, this article is directed towards evaluating attempts to facilitate Arabic grammar, taking into account the general context in which those attempts occurred without approaching those attempts with impressionistic judgments based on the idea of sanctification and rejection of the other, all in accordance with the requirements of conscious scientific consideration. It is no secret that Al-Makhzoumi is one of the late Arab grammarians who demonstrated his mastery and knowledge of ancient Arabic grammar, in addition to his many scientific contributions that are praised;Therefore, he was chosen in order to consider his critical model and the theoretical and methodological alternatives he presented that, in his opinion, establish a practical and scientific Arabic grammar free from logical impurities and philosophical complexities. It is hoped that the results of this article will address most of the problems related to this topic and answer the central questions raised by the researchers, leading to the advancement of Arabic grammar and placing it in its current scientific context.